ORGANIZATIONAL GOOD PRACTICES FOR THE INTEGRATION OF THE ICT IN THE EDUCATION SYSTEM OF EXTREMADURA - Mª José Sosa Díaz; Sara Peligros García; Dionisio Díaz Muriel (Ediciones Universidad de Salamanca, 2010)
<!-- @page { margin: 0.79in } P { margin-bottom: 0.08in } --> The present paper tries to release some organizational Good Practices for the integration of the ICT's carried out by the Education System in Extremadura. For this, in a first moment, a theoretical review about the concept of Good Practices has been done, establishing some indicators which permit us identify Good Practices regarding the application of the ICT within Primary and Secondary schools, and specially pointing out the indicators that refer to organizational aspects in the educational establishments and classrooms. Secondly, the politics for the integration of New Technologies conducted by Junta de Extremadura are analyzed, emphasizing the figure of the ICT Coordinator as a quality measure, as well as the technological tools for school management and controlling the classes. Finally, we present the results obtained from several interviews that were made to different members of the school community, all in a broader investigation where diverse case studies of Primary and Secondary schools considered as Good Practices with ICT were effectuated.